Retrospective Analysis of Clinical Profile, Management and Outcomes of Pulmonary Embolism in Western Nepal, A Single Center Study - KC, Bishal; Gautam, Samir; Dhungel, Sachin; Khan, Mazhar; Ghimire, Jeet Prasad; Shakya, Abhishesh; Nepali, Ram; Shrestha, Kabindra; Adhikari, Roshan; Thapa, Babita (Journal of National Heart and Lung Society Nepal, 2025)
Background: Pulmonary embolism (PE) is a potentially life threatening condition. Symptoms can be vague mimicking other conditions. Severity depends on the size and location of the embolism. A thorough medical history is crucial to identify the risk factors. This study aims at identifying clinical presentations, management and outcome of PE. Methods: This was a retrospective analysis of the patients presenting with acute PE for four years, from May 2020 to May 2024 at Gautam Buddha Community Heart Hospital. Results: Altogether 51 patients admitted for acute PE were included in the study. The mean age was 54.39±18. Majority were male 30(58.8%). The most common age group affected was 41–60 years (43.1%). The majority of them were categorized as low risk 37(72.5%). Clinically 16 patients (31.4%) had provoked conditions, whereas 35 patients (68.6%) presented with non-provoked conditions. The most common clinical presentation was shortness of breath 44(86%) followed by chest pain 15(23.4%). The most common ECG and Echocardiogram finding was sinus tachycardia 43(84.4%) and dilated right atrium and right ventricle 45(88.2%) respectively. Direct acting anticoagulants was used in 17(33.3%) patients. The mean hospital stay for the cohort was 4.4 ± 1.8 days. There were five mortalities with mean simplified PESI score of 3±0.7. Conclusion: Acute PE is a life-threatening condition resulting from the obstruction of the pulmonary arteries. Prompt diagnosis and treatment are crucial to reducing morbidity and mortality.